“Training and Capacity Building for Eligible SMEs” Kewirausahaan Sosial bagi Pemuda Bidang Pertanian pada Program Youth Entrepreneurship And Employment Support Service (YESS) di Bogor Jawa Bara - Nanik Risnawati (E-Coops-Day, 2023)
Agricultural business is one of the business fields that is mostly engaged in by the Indonesian population. However, currently, the interest of the younger generation to do business in agriculture is decreasing and fading. Meanwhile, the need for agricultural products, especially food, is even higher as the population continues to increase. Therefore the government launched the YESS program aimed at helping young people to be willing and able to take part in the world of agriculture.One of the YESS program activities is the provision of Entrepreneurship and Social Entrepreneurship training. This activity was attended by 24 participants who work as Offtaker. Participants who work in agriculture, either farm or off-farm personally, their business is quite good, some of them have even carried out export business, such as to the Netherlands, Malaysia, and several European countries. After measuring the quality of their personal entrepreneurship, it can be seen that theparticipants generally already have good entrepreneurial qualities with a score above 15. It's just that what still needs improvement or improvement is self-confidence and the ability to seek business opportunities. Because Oftaker It is hoped that it can accommodate the business results of potential beneficiary novice farmers (CPM) so participants are instructed to learn how to develop social entrepreneurship, so that awareness grows order to be able to jointly benefit from the business activities they carry out, not only for themselves but also the people who can be helped.